Optimizing Communication Skills: Public Speaking and Positive Social Media Digital Footprint Training For Dhammasavana Tambora Junior High School Students, West Jakarta - Satya Candrasari; Alicia Angelina Baso; Haniifah Nabiilah; Rama Andika; Randy Liaw; Reonald Purnama Purba (ABDIMAS Jurnal Pengabdian Kepada Masyarakat, 2024)
The Public Speaking and How to Design a Positive Digital Footprint on Social Media program is a community service initiated by Institut Teknologi dan Bisnis Kalbis communication lecturer as well as Corporate Social Responsibility (CSR) class students. This activity was held at Dhammasavana Tambora Junior High School, West Jakarta, with 30 students from the 8th grade participating. The training emphasized on public speaking skills as well as an understanding of positive digital footprints. The training material was delivered by the Corporate Social Responsibility class students with the aim of introducing and providing training in public speaking skills, focusing on speech preparation and structure. This material is very important for students at an age where they are very close to the digital world, namely social media and the need to apply public speaking skills to support their learning at school. The implementation of the community service resulted in a more engaged environment, with students actively participating in debates and assignments. The relevance of successfully integrating public speaking and social media training, the development of social communication skills, and the importance of digital etiquette awareness is highlighted in the conclusion. This practice is expected to continue in high schools, benefiting students' abilities and understanding.